E-Budgeting and the Effectiveness of Pro-Poor Public Spending: An Institutional Governance Perspective from Local Government in Indonesia - Sawaluddin Fitri Tanjung; Syamsurijal Tan; Achmad Hizazi; Zamzami Zamzami (Politeknik Siber Cerdika Internasional, 2026)
Background: Despite continuous increases in local fiscal capacity and budget allocations, governance constraints—such as weak transparency, accountability, and coordination—often undermine the effectiveness of pro-poor public spending. From an institutional governance perspective, these constraints challenge not only policy performance but also the sustainability of poverty alleviation efforts. Objective: This study examines the relationships among local government budget management quality, e-budgeting implementation, and the effectiveness of pro-poor public spending at the subnational level in Indonesia. Methods: Drawing on survey data collected from officials in local government agencies in West Tanjung Jabung Regency, the study employs Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze direct and indirect relationships among multidimensional governance constructs. Results: The results indicate that the Regional Revenue and Expenditure Budget (APBD) does not have a significant direct effect on poverty reduction (β = −0.036, p = 0.776). However, APBD has a positive and significant effect on E-Budgeting implementation (β = 0.667, p < 0.001), while E-Budgeting significantly contributes to poverty reduction (β = 0.673, p < 0.001). These findings suggest that effective E-Budgeting implementation plays a crucial role in enhancing transparency, accountability, and budget efficiency, thereby supporting poverty reduction efforts in Tanjung Jabung Barat Regency. Conclusion: By strengthening transparency, accountability, budget traceability, and interagency coordination, e-budgeting enhances consistency between budget planning and implementation processes and supports the sustainable effectiveness of pro-poor public spending in decentralized government systems. Theoretically, this study contributes to the public financial management and digital governance literature by positioning e-budgeting as an institutional mediating mechanism linking budget quality to sustainable policy implementation.